Improving Student Learning Outcomes in Light and Optical Instruments Using Team Teaching Methods with Crossword Puzzle Media - Cicilia Nuning Tiastiti; Wahyu Fitria Ariyanti; Munirah Mubarak Alquaimi; Wan Long Chiong (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: This research aims to determine the improvement in student learning outcomes regarding light and optical devices in class VIII junior high school through the team teaching method and crossword puzzle learning media. Methodology: This research is a type of classroom action research. The subjects in this research were 30 students in class VIII A of Junior High School 2 Tuntang. Data collection techniques in this research used tests, observation, documentation. Data analysis in this research was carried out descriptively qualitatively and quantitatively. Main Findings: The research results showed that cycle I produced 8 students with a percentage of 26.7% who completed the minimum completion criteria and there were 22 students who had not completed it with a percentage of 73.3%. Meanwhile, cycle II produced 26 students who completed the minimum completion criteria with a percentage of 86.7%, while there were 4 students who had not completed it with a percentage of 13.3%. This was marked by an increase in the results of classical completion criteria in cycle I which was only 26.7% to 86.7% in cycle II. The team teaching method used in combination with crossword media makes students interested in new ways of learning. Novelty/Originality of this study: This study explores improving student learning outcomes in light and optical instruments using innovative methods, including team teaching and interactive crossword puzzles. The integration of crossword puzzles into teaching materials provides a unique and engaging learning experience, enhancing students' understanding of the subject.